Suppression of cathepsin K biomarker in synovial fluid as a free-drug–driven process. (7th January 2019) - Ma, Bennett; Wesolowski, Gregg; Luo, Bin; Lifsted, Traci; Wessner, Keith; Adamson, Gary; Glantschnig, Helmut; Lubbers, Laura S
Cathepsin K (CatK) inhibitors exhibited chondroprotective and pain-reducing effects in animal models, however, improvements were relatively modest at dose levels achieving maximal suppression of CatK biomarkers in urine. In this report, a previously characterized CatK inhibitor (MK-1256) is utilized to explore the potential of reduced target engagement and/or suboptimal exposure (free drug) as limiting factors to the pharmacological potential of CatK inhibitors in the knee joint. Following oral administration of MK-1256 at a dose level achieving maximal inhibition of urinary biomarker (helical peptide) in dogs, full suppression of the biomarker in synovial fluid was observed. Subsequent tissue distribution studies conducted in dogs and rabbits revealed that MK-1256 levels in synovial fluid and cartilage were consistent with the free-drug hypothesis. Reasonable projection (within twofold) of drug levels in these tissues can be made based on plasma drug concentration with adjustments for binding factors. These results indicate that the previously observed efficacies in the animal models were not limited by compound distribution or target engagement in the knee tissues.